Peranan Model Pembelajaran Project Based Learning Fasilitas Belajar Dan Variasi Mediaterhadap Hasil Belajar IPS - Nur imamah Utami (Jurnal Penelitian dan Pendidikan IPS, 2019)
Abstract. Based on the result, most of teachers still using speech method so that the student less enthusiast in teaching-learning process of geography. The availability of learning facility and then the media variation that used by teacher yet not maximal so that the achievement still low. The aim of this study is to analyze the effect of project based learning model, learning facility, and media variation toward the achievement of IPS student. This study is quantitative study by using 89 students as saturation sampling. The instrument in collecting data are documentation and questionnaire. The technique of data analysis are multiple regression analysis, classic assumption test, and hypothesis test. (1) There is a significant effect between the combination of PjBL learning model, facility learning, and media learning variation toward IPS student achievement. (2) There is a significant effect between PjBL learning model with IPS students achievement. (3) There is a significant effect between facility learning with IPS student achievement. (4) There is a significant effect between media variation with IPS students achievement. Teacher should be develop some variative model in teaching-learning process so that the student will be more active in it, one of the example is by using project based learning model, beside of that parents and teachers should grow a motivation to the student to increase the facility learning in the school or in the house. The aim is to make the student get maximum achievement.